2009
DOI: 10.1111/j.1538-7836.2009.03326.x
|View full text |Cite
|
Sign up to set email alerts
|

Dose escalation of low molecular weight heparin to manage recurrent venous thromboembolic events despite systemic anticoagulation in cancer patients

Abstract: To cite this article: Carrier M, Le Gal G, Cho R, Tierney S, Rodger M, Lee AY. Dose escalation of low molecular weight heparin to manage recurrent venous thromboembolic events despite systemic anticoagulation in cancer patients. J Thromb Haemost 2009; 7: 760À5. Summary. Background: Cancer patients with venous thromboembolism (VTE) are at high risk of recurrent VTE despite standard anticoagulation. To date, very little published literature is available to guide the treatment of cancer patients with recurrent VT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
1
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 206 publications
(122 citation statements)
references
References 27 publications
2
105
1
11
Order By: Relevance
“…Only a very small number of patients successfully managed using further dose escalation of lmwh for additional recurrent events have been reported in the literature 20 . Although the use of plasma antifactor Xa has been suggested to guide further dose escalation 28 , our recommendation is based solely on expert opinion.…”
Section: Recurrent Cancer-associated Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Only a very small number of patients successfully managed using further dose escalation of lmwh for additional recurrent events have been reported in the literature 20 . Although the use of plasma antifactor Xa has been suggested to guide further dose escalation 28 , our recommendation is based solely on expert opinion.…”
Section: Recurrent Cancer-associated Thrombosismentioning
confidence: 99%
“…In patients treated for cancerassociated thrombosis, the 6-month incidence of recurrent vte is 14% for those receiving warfarin and 7% for those receiving lmwh monotherapy 25 . Three retrospective cohort studies reported on the efficacy and safety of a full therapeutic dose of lmwh for the management of recurrent vte despite anticoagulation with warfarin 20,26,27 . Similarly, two retrospective cohort studies assessed the use of lmwh dose escalation for patients with recurrent vte despite treatment with lmwh 20,26 .…”
Section: Recurrent Cancer-associated Thrombosismentioning
confidence: 99%
“…The 2013 international CPGs relied on one retrospective cohort study 81 Symptomatic catheter-associated thrombosis occurs in 3·0-5·0% of patients with cancer requiring venous access, which increases to as much as 30·0% when including asymptomatic cases. 21 Since 2013, one new retrospective study 83 One meta-analysis 85 assessed the benefi t-to-risk ratio of diff erent anticoagulants in 2564 patients with catheterassociated thrombosis.…”
Section: Vte Recurrence In Patients With Cancer On Anticoagulation Mementioning
confidence: 99%
“…However, there is no high‐quality evidence to guide practice in this situation. Recommendations from major guidelines including changing oral anticoagulants to LMWH or escalating LMWH doses by 20%‐25% are based on limited retrospective studies 52, 53, 54. The results of a registry study addressing this issue were reported recently, including 212 cancer patients with recurrent VTE on anticoagulation 55.…”
Section: Treatment Of Cancer‐associated Thrombosismentioning
confidence: 99%